An in vitro appraisal of properties of dental amalgam using commercially available and ayurvedically recycled mercury: Recycle and reuse - Pandiar D.; Baranwal H.C.; Chattopadhyay K.; Kumar P. (My University, 2025)
Introduction: With the introduction of tooth-colored restoration material, the usage of amalgam has reduced over years. However, results regarding toxicity and health concerns are conflicting. Based on the concept of recycle and reuse, we previously used an ayurvedic method for purification of excess mercury obtained from dental operatory. In the present study, we aimed to evaluate the properties of dental amalgam using commercially available and ayurvedically recycled mercury. Materials and Methods: Samples were prepared for analysis of mean compressive strength, Vickers hardness number, and coefficient of friction dental amalgam using commercially available and ayurvedically recycled mercury. Further analysis was done using scanning electron microscopy. The data were presented on Microsoft Excel Spreadsheet 2013 and statistical analysis was done on IBM SPSS software (IBM Analytics) and OriginPro 8 software. Results and Conclusion: No statistically significant difference was found in properties of dental amalgam prepared using commercially available and ayurvedically recycled mercury. Although not statistically significant, early compressive strength and hardness of amalgam using ayurvedically recycled mercury were comparatively higher, which may be attributed to residual amounts of silver, tin, and copper acting as nucleating agent for faster setting reaction. © 2018 Journal of Conservative Dentistry.